2019
DOI: 10.1016/j.ymgmr.2019.100532
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive clinical, biochemical and genetic screening reveals four distinct GBA genotypes as underlying variable manifestation of Gaucher disease in a single family

Abstract: Gaucher disease (GD) is a lysosomal storage disorder that is associated with bi-allelic pathogenic variants in GBA. Its wide clinical spectrum, ranging from mild organomegaly to significant skeletal and neurological involvement, is partially explained by genotype-phenotype correlations. We present a family, in which all members over two generations presented with at least splenomegaly. Comprehensive clinical, biochemical and genetic workup was required to diagnose GD, which is caused by as many as four distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…As mentioned above, the genotype of one index patient (patient 14, Table S2) contained three changes, however, the p.Arg368His alteration could not be phased, and thus it remains unclear whether it comprises an allele with p.Asn409Ser or p.Leu483Pro. Of note, the marriage of two of our index patients (patients 31 and 32, Table S2) resulted in three affected offspring (patients 33‐35) with novel genotypes emerging from the combination of their parental alleles, as previously reported 14 . Thus, overall, our patients harbored 15 different genotypes (Table S2).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…As mentioned above, the genotype of one index patient (patient 14, Table S2) contained three changes, however, the p.Arg368His alteration could not be phased, and thus it remains unclear whether it comprises an allele with p.Asn409Ser or p.Leu483Pro. Of note, the marriage of two of our index patients (patients 31 and 32, Table S2) resulted in three affected offspring (patients 33‐35) with novel genotypes emerging from the combination of their parental alleles, as previously reported 14 . Thus, overall, our patients harbored 15 different genotypes (Table S2).…”
Section: Resultssupporting
confidence: 69%
“…Among these 36 individuals, 28 were unrelated index patients (4 familial and 24 sporadic; Table S2) and 8 were affected family members. Notably, two unrelated index patients formed one of the families through marriage 14 . The three remaining families consisted of sibling pairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another three studies providing information on plasma lyso-Gb1 as a prognostic biomarker were identified. Firstly, in a family in which all members over two generations presented with splenomegaly owing to four distinct GBA genotypes, a plasma lyso-Gb1 level spanning more than one order of magnitude correlated well with the presumed pathogenicity of the genotypes and with hepatosplenomegaly, thrombocytopenia, and bone pain [ 123 ]. Secondly, moderate-to-strong correlations between plasma lyso-Gb1 and spleen volume, liver volume, and Hb but not platelet count at baseline were detected in eliglustat clinical trials of treatment-naïve adults with type 1 GD [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features are diverse according to the type of GD [6,8,9]. In type 1, the accumulation of substrate results in the enlargement of the liver and spleen, fatigue, growth retardation, delayed puberty, bleeding disorders, pancytopenia, and painful bone crisis related to vascular diseases or mechanic effects [6,8,10].…”
Section: Introductionmentioning
confidence: 99%